Facial Expression Recognition in Children with Cochlear Implants and Hearing Aids - Wang, Yifang; Su, Yanjie; Yan, Song (Frontiers in Psychology, 2016)
Facial expression recognition (FER) is important for effective communication. To explore whether the development of FER was delayed, 22 children with a Cochlear implant (CI) or Hearing aid (HA) and 22 children with normal hearing (matched by age and gender) completed labelling and matching tasks to identify four basic emotions (happiness, sadness, anger, and fear). The results showed that children with a CI or HA were developmentally delayed not only in their emotion-labelling (verbal) tasks but also in their emotion-matching (nonverbal) tasks. How difficult it was to recognize different emotional expressions was consistent between the verbal and nonverbal tasks though labelling was more difficult than matching. Additionally, happy and sad faces were the easiest to recognize, followed by angry and fearful faces.